2019
DOI: 10.1021/acs.energyfuels.9b02259
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Droplet Burning Behavior of Diesel–Palm Biodiesel Blends

Abstract: Diesel−palm biodiesel blend could be an attractive fuel for diesel vehicles owing to its better physicochemical properties compared to those of fossil diesel. This study comprehensively investigates the combustion behavior of diesel droplet blended with palm biodiesel at 20% v/v, 40% v/v, and 60% v/v (i.e., B20, B40, and B60, respectively). Droplet combustion experimental results show that the B60 and palm biodiesel droplets exhibit a more prominent blue flame and less sooty flame compared to diesel droplet. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
5
0
4
Order By: Relevance
“…Pembakaran droplet tunggal akan merepresentasikan droplet yang terbentuk pada pembakaran spray. Pada beberapa penelitian terdahulu, uji pembakaran droplet banyak dilakukan pada minyak nabati dan biodiesel yang terdiri atas senyawa multikomponen [18][19][20][21][22]. Pada penelitian tersebut, fenomena-fenomena yang diamati selama pembakaran droplet dikaitkan dengan konsentrasi senyawa yang paling dominan dalam bahan bakar.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Pembakaran droplet tunggal akan merepresentasikan droplet yang terbentuk pada pembakaran spray. Pada beberapa penelitian terdahulu, uji pembakaran droplet banyak dilakukan pada minyak nabati dan biodiesel yang terdiri atas senyawa multikomponen [18][19][20][21][22]. Pada penelitian tersebut, fenomena-fenomena yang diamati selama pembakaran droplet dikaitkan dengan konsentrasi senyawa yang paling dominan dalam bahan bakar.…”
Section: Pendahuluanunclassified
“…Droplet pada tahap awal pembakaran mengalami kavitasi, pembengkakan, dan terdistorsi, sehingga menghasilkan perubahan diameter yang flukuatif. Fluktuasi ini dapat dikaitkan dengan proses yang terjadi pada periode ini, terdiri atas kavitasi yang menyebabkan terbentuknya rongga dalam droplet, swelling yang menghasilkan pembengkakan akibat adanya kavitasi, dan secara bersamaan terjadi pembakaran pada permukaan droplet [18,20,39]. Kavitasi dan swelling menyebabkan peningkatan diameter droplet, sedangkan proses pembakaran pada permukaan droplet menyebabkan diameternya berkurang.…”
Section: Evolusi Diameter Dropletunclassified
See 1 more Smart Citation
“…While many studies have examined the combustion characteristics of palm biodiesel droplet (Ooi et al 2019(Ooi et al , 2017Muelas et al 2019), only a few studies have investigated its evaporation characteristics. Hashimoto et al (2015) studied the evaporation of PME, its constituent esters, diesel, and n-hexadecane at elevated temperatures ranging from 473 to 873 K. All fuels were observed to have increased average evaporation coefficients with the increase in temperature.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on biodiesels and excellent reviews on this topic (both fundamental studies and biodiesel utilization) can be found in the literature. ,, The common findings noted in the current literature include the following: (i) biodiesels can be made from different feedstock and could be a potential candidate to partly replace fossil diesel used in compression ignition engines , and these biofuels could be blended with fossil diesel with or without additives, (ii) biodiesels have a higher cetane number but a lower calorific value and higher viscosity compared to fossil diesel, , and (iii) fueling engines with biodiesels can help to decrease specific particulate matter in mass basic, while the effect of biodiesels on NO x formation and particle number and size distribution is not fully understood. , Further investigations of physical and chemical properties of biodiesels made from different feedstock are essential to have a comprehensive understanding of the engine performance when operating with biodiesels. The impact of FAME profiles, especially oxygen content, on the properties of biodiesels made from different feedstock, and the influence of fuel properties on fuel atomization and evaporation, according to the authors’ knowledge, is not quite clear in the literature.…”
Section: Introductionmentioning
confidence: 99%